PENERAPAN SISTEM INFORMASI AKADEMIK (SIA) SEBAGAI UPAYA PENINGKATAN EFEKTIFITAS DAN EFISIENSI PENGELOLAAN AKADEMIK SEKOLAH - Riyadi Purwanto (P3M Politeknik Negeri Indramayu, 2017)
Information Technology has provided an important role as a medium of information and communication in the field of education, one of them in School Academic Management. Implementation of Academic Information System as one way to increase effectiveness and efficiency of academic management include new student enrollment, student and teacher data management, management of lesson schedule, and student value processing. Academic Information System developed as an information service in the form of data related to academic data. In the development of Academic Information System, the methodology that can be used is Waterfall methodology which consists of several stages, among others: 1)Planing stage that is discussing the planning of the system to be developed, 2)Stage Analysis is to analyze the running system and the analysis of functional and non functional needs, 3)Design stage that is designing and designing system, and 4)Implementation Phase that is production of application and testing.The results showed that Academic Information System can improve the effectiveness and Efficiency of School Academic Management. In terms of effectiveness, academic information system can be used to improve communication and organize academic data accurately and accurately, while in terms of efficiency, academic information system can accelerate the academic management process, reduce operational costs (low cost and paper less) and reduce human error in processing student value